MONEY ATTITUDES, BUDGETING AND HABITS - ADRIAN FURNHAM; MARK FENTON-O’CREEVY (Journal of Financial Management, Markets and Institutions)
This study was concerned with the correlates of attitudes to, and habits surrounding money, particularly budgeting. It involved a secondary analysis of a representative (UK) sample of adults who completed a questionnaire that enquired into such things as their saving and spending habits, and investments. We drew on data from 1767 participants and looked specifically at demographic correlates (age, gender, income), as well as money attitudes, spending habits and their self-rated financial literacy. Our central interest was how specific beliefs about money, impulsive spending, and financial literacy are related to regular saving, spending and investment. Through correlation and regression analyses, we were able to show that household income was a major correlate of these behaviors, as were participant gender and age. We paid particular attention to the money attitude variable which suggested that those who saw money primarily as a source of security tended to be savers rather than investors and had more disposable cash. Implications of the findings and limitations of the study are discussed, including implications for detecting and advising those with money-related issues.